PRE-SEQUENCES AND SPEECH ACTS IN CEBUANO RADIO HEALTH COMMERCIALS IN CEBU CITY - Apalla, Ceska Marie R; San Juan, Keeshia Joy S; Maxilom, Rowanne Marie R (Universitas Muhammadiyah Surakarta, 2017)
This research attempted to identify and analyze the Cebuano-Bisaya radio health commercials using Schegloffâs (2007) framework on pre-sequences with the support of Yuleâs (1996) speech act theory. Thirty (30) Cebuano-Bisaya radio health commercials were gathered from two selected radio stations. The results revealed that representatives were the most dominant function in speech acts that reflected in pre-sequences specifically with pre-offers and pre-announcements throughÂ dramaÂ andÂ testimonialÂ categoriesÂ whichÂ areÂ oftenÂ usedÂ inÂ medicinal productÂ commercials.Â InÂ advertisingÂ strategies,Â Cebuano-BisayaÂ commercials useÂ RepresentativesÂ andÂ ExpressiveÂ asÂ persuasiveÂ devicesÂ inÂ addressingÂ the advertisersâ intendedÂ messageÂ toÂ theÂ targetÂ audience.Â Also,Â Cebuano-Bisaya commercials used Representatives and Expressive as an appeal to suggest an intention for the listener to buy advertised products.Keywords: Cebuano, commercial, health, pre-sequences, radio, speech acts